2018
DOI: 10.3390/rs10071002
|View full text |Cite
|
Sign up to set email alerts
|

Inland Water Atmospheric Correction Based on Turbidity Classification Using OLCI and SLSTR Synergistic Observations

Abstract: Atmospheric correction is an essential prerequisite for obtaining accurate inland water color information. An inland water atmospheric correction algorithm, ACbTC (Atmospheric Correction based on Turbidity Classification), was proposed in this study by using OLCI (Ocean and Land Color Instrument) and SLSTR (Sea and Land Surface Temperature Radiometer) synergistic observations for the first time. This method includes two main steps: (1) water turbidity classification by the GRA index (GRAdient of the spectrum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 78 publications
2
16
0
Order By: Relevance
“…Similar to the previous study [23], R rs (400), R rs (412), and R rs of NIR bands longer than 709 nm were omitted in the classification due to the poor performance of the atmospheric correction. For OLCI-derived R rs , POLYMER and C2RCC had obvious overcorrection of R rs , consistent with the study of Bi et al (2018) [51] in Lake Taihu and Lake Hongze. It was also shown that C2RCC exhibited good performances from 490 to 709 nm, and poor performances in the blue (400, 412, and 443 nm) and NIR wavebands (754-865 nm) for the highly absorbing waters in the Baltic Sea [60].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to the previous study [23], R rs (400), R rs (412), and R rs of NIR bands longer than 709 nm were omitted in the classification due to the poor performance of the atmospheric correction. For OLCI-derived R rs , POLYMER and C2RCC had obvious overcorrection of R rs , consistent with the study of Bi et al (2018) [51] in Lake Taihu and Lake Hongze. It was also shown that C2RCC exhibited good performances from 490 to 709 nm, and poor performances in the blue (400, 412, and 443 nm) and NIR wavebands (754-865 nm) for the highly absorbing waters in the Baltic Sea [60].…”
Section: Discussionsupporting
confidence: 86%
“…If D m 2 was lower than the threshold value D t 2 , the spectrum x belongs to the class; if D m 2 > D t 2 , the pixel would be recognized as an unclassified type. In addition, the current optical classification tool built in SNAP software [22] was also tried in this study, but it did not perform well due to the failure of atmospheric correction in the study region [48,51]. When applied to the satellite OLCI data, the wavelengths selected need to be effective in separate water types.…”
Section: Type-labeling Of the Satellite R Rs (λ)mentioning
confidence: 99%
“…Almost all available AC algorithms specially designed for coastal and turbid waters were considered. Due to the unavailability of codes, some AC algorithms were omitted from the present study [21,42,63,64]. Table 2.…”
Section: Selected Atmospheric Correction Algorithmsmentioning
confidence: 99%
“…Many studies did assess the performance of existing AC algorithms in moderately turbid waters for different satellite sensors such as SeaWiFS (Sea-Viewing Wide Field-of-View Sensor) [28], MODIS-Aqua [29], GOCI (Geostationary Ocean Color Imager) [30], L8-OLI [31][32][33][34][35][36], S2-MSI [36][37][38][39][40][41] and S3-OLCI [42,43]. None of these studies considered the case of highly turbid waters for S3-OLCI.…”
mentioning
confidence: 99%
“…The validation work exposed here is the first done over French coastal waters for the OLCI sensor. Actually, a similar work was published for OLCI AC development and validation, but over inland waters and not coastal waters [52].…”
Section: Introductionmentioning
confidence: 99%